(untitled) (International Journal of Engineering and Computer Science, 2016)
Traditional teaching methods rely on written exercises, books, oral lectures and blackboards as the primary vehicles to spread knowledge. Nevertheless, technological process brought new opportunities to teach and educate, such as using video games that spiced up curiosity and fired reviews amongst many educators and researchers. Research shows that video games have a great potential to improve the learning experience and learning outcomes. These facts among others led to this research.